HI 1628: A high yielding wheat variety for timely sown, restricted irrigation conditions of North Western Plains Zones of India - Singh, Jang Bahadur; Prasad, Sakuru Venkata Sai; Ambati, Divya; Phuke, Rahul Madhav Rao; Prakasha, Thorehalli Linganna; Mishra, Akilesh Nandan; Sharma, Kailash Chandra; Singh, Anil Kumar; Singh, Gyanendra Pratap; Sharma, Jai Bhagwan; Singh, Pradeep Kumar; Yadav, Harikrishna; et al. (Journal of Cereal Research, 2021)
HI 1628 has average yield of 50.4 q/ha over the zone and showed significant superiority over the checks; with a potential yield of 65.1 q/ha. It has shown excellent and wider adaptation and significantly superior performance across different irrigation regimes over the checks with an average yield of 45.5q/ha. It showed high levels of field resistance to yellow and brown rusts. It is a good quality bread wheat genotype with excellent chapati quality (7.56), bread quality (7.64), biscuit spread factor (8.27) and high sedimentation value (56.6 ml). It has high protein content ( 11 %) and protein quality (Glu score of 8/10) for high molecular weight subunits and presence of 5+10 subunit of Glu-D1 reflecting higher gluten strength in this genotype.